Efeito da remoção da vegetação ripária sobre a rede trófica de uma assembleia de peixes de um riacho neotropical - Manoel, Pedro Sartori [UNESP]; Uieda, Virginia Sanches [UNESP] (Instituto de Pesquisas Ambientais em Bacias Hidrograficas (IPABHi), 2018)
The study of the diet of fish is an important tool to assess different levels of environmental degradation, since the availability of food in the environment is a key factor for the fish occurrence. The removal of riparian vegetation usually degrades environmental quality, as this vegetation has an important role in providing energy to the ecosystem. This study investigates the effects of the removal of riparian vegetation on the fish assemblage trophic network. The study was carried out in two stretches of a southeastern Brazilian stream, one in a forest fragment and another in a pasture, during the wet and dry seasons of 2014. We analyzed the items consumed by each fish species using the frequency of occurrence and area of each item, which were combined to calculate the alimentary index, which was used to determine the food niche overlap of the fish and the specialization index of the trophic network. Aquatic Hexapoda, vegetal debris and organic matter dominated the trophic network of the two stretches. We detected higher values of food niche overlap in the forested stretch and more complex trophic networks in the pasture stretch. We found few seasonal variations in the items consumed and calculated indices in both stretches studied. The presence of grass on the banks in the pasture stretch and the importation of food resources from the upstream area may have provided a higher diversity of resources and consequently showed a more complex trophic network when compared to the forested stretch.
Effect of the riparian vegetation removal on the trophic network of neotropical stream fish assemblage
Keywords: Fish diet; Food niche overlap; Trophic organization